Deteksi Urolithiasis pada Sapi Bali (Bos Sondaicus) yang Dipelihara Secara Semi Intensif di Desa Noelbaki Kecamatan Kupang Tengah - Windra Triven Benu; Yohanes TRMR Simarmata; Herlina U Deta (Jurnal Veteriner Nusantara, 2023)
One of the Urolithiasis diseases in Bali cattle (Bos sondaicus) is crystal stones found in the urinary tract. These stones are formed in the kidney pelvis, ureter, bladder and urethra which can enlarge and can cause pain, bleeding or infection in the urinary tract forming crystals in the urine Urinary stones can move down along the ureter and enter the urinary bladder and when they occur deposition, the crystallized particles can increase in size so that they can cause disturbances in cattle. This study aims to identify and determine high levels of calcium oxalate in the kidneys can also affect the occurrence of crystal stones in male Bali cattle in Noelbaki Village, Central Kupang District, Kupang Regency. Macroscopic examination of urine sediment in Bali bulls, namely the examination of urine color, pH examination, and examination of Urine Specific Gravity and Microscopic Examination including Dicentrifuge and Calcium Oxalate Test Kit on 50 male Bali cattle. The results of the urine examination of male Bali cattle showed 5 positive types of crystals, 3 calcium oxalate and 2 sturvite.